P59 The utilisation of flow cytology and evaluation of CD4/CD8 ratios from mediastinal and hilar lymph node sampling by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA): experiences at oxford university hospitals foundation trust (OUH). (12th November 2019) - Achaiah, A; Lomas, O; Moore, A; Wrightson, J; Sykes, A
Abstract : Introduction: EBUS-TBNA is widely used in investigating mediastinal lymphadenopathy of unclear cause and can negate the need for invasive and higher risk procedures such as mediastinoscopy. Mediastinoscopy is still required in non-diagnostic cases and we assessed whether addition of flow cytometry could add further useful information to standard testing Aim: Characterise CD4/CD8 profiles of mediastinal and hilar lymphadenopathy by EBUS–TBNA sampling and flow cytometry. Compare with simultaneous cytology sampling to determine if CD4/CD8 profiles correlate with any particular disease state which may, in cases of uncertainty, assist diagnosis. Methods: 106 EBUS-derived samples of lymphoid tissue were obtained between October 2015 and October 2018. 85 samples were analysed by flow cytometry and diagnostic cytology. Sampling and analysis was performed in house by OUH. Samples were categorised as either Sarcoid or Not Sarcoid (sub-divided into Lung cancer, Haematological cancer or Non-malignant). Statistical analysis was performed using Mann-Whitney Test for Two Independent Samples. Results: 3 samples were inadequate for flow cytology and excluded. From histological analysis 44 cases were consistent with Sarcoidosis. 12 lung cancer, 2 haematological malignancy. In 21 cases no malignancy was identified. In 5 of these diagnosis remained uncertain and were kept under observation. Median CD4/CD8 ratio 3.0 (SE ±0.42). In 2 cases EBUS-TBNA sampling was non-diagnostic; diagnosis later confirmed by mediastinoscopy (1 case TB and 1 case Lymphoma). CD4/CD8 profiling not used in diagnosis and therefore did not influence decision to proceed to mediastinoscopy. Table 1 details flow cytometry results. Discussion: Our findings support current literature that CD4/CD8 ratios from EBUS-TBNA sampling of Mediastinal lymph nodes are higher in Sarcoidosis. From our data CD4/CD8 ratios were significantly lower in the Non-sarcoid group. Especially between Lung cancer Vs Sarcoid (p=0.0006) and Non-malignant Vs Sarcoid groups (p=0.007). CD4/CD8 ratios were not significantly different between Lung cancer and Non-malignant groups. Our study is limited by small sample size. Conclusion: Flow cytometry profiling of CD4/CD8 ratios from Mediastinal lymph nodes suggested that higher ratios may favour Sarcoid but its utility, at present, is unlikely to be helpful in clinical practice.